Use of participatory forum theatre to explore HIV/AIDS issues in the workplace - Emma Durden; Dominique Nduhura (Communicare)
The continued success of entertainment education programmes around the world has seen an increase in the use of theatre for HIV/AIDS interventions. Both UNAIDS and UNESCO recommend the use of such cultural strategies for HIV/AIDS awareness. A brief survey of current evaluations in this field reveals such projects in Kenya, Angola, Mozambique, the Netherlands and Honduras, amongst other countries. Forum theatre is reported as being used as a technique to deepen understanding of HIV/AIDS issues in programmes in Georgia, Tanzania, Burkina Faso and South Africa (The Communication Initiative, 2007). This paper explores the application of participatory theatre techniques in a South African factory environment in 2003. It investigates the conditions and context for the project, some of the theoretical underpinnings of the forum theatre concept, and the reception of the project by the factory audience. Essentially, the paper seeks to determine whether forum theatre is an appropriate strategy to use for HIV/AIDS awareness in this environment.